Reality and Culture : Essays on the Philosophy of Bernard Harrison. - Hanna, Patricia. (Value Inquiry Book Series, 2014)
More than being a volume about the philosophy of Bernard Harrison, this volume is about how Harrison conceptualizes the creation of the human world. One might be tempted to classify Harrison as a major voice in many diverse discussions-philosophy of literature, philosophy of language, philosophy of mind, color studies, epistemology, metaphysics, moral philosophy, philosophy of culture, Wittgenstein, antisemitism, and more-without recognizing a unifying strand that ties them together. Nothing could be farther from the truth. Harrison contests and destabilizes a persistent and misleading alignment of culture with subjectivity-whether found in unexamined distinctions between nature and culture or appearance and reality. His general aim has been to undermine the belief that human culture deals in smoke and mirrors, and that the only realities are those of extra-human nature. He emphasizes the paraxial foundation of meaning, and argues that the creative inventions of language and culture are as real as any extra-linguistic reality. While granting the existence of extra-human reality, he holds it to be, in itself, conceptually unorganised, but nevertheless cognitively accessible by way of sense-perception and physical manipulation. This volume offers new critical essays that examine Harrison's corpus, written by distinguished voices in philosophy and literary studies. It bridges many of the abysses of conflicting opinion opened by the culture wars of the past half-century. Importantly, it includes an opening essay by Harrison that elucidates the unifying strand running through his variegated philosophical writings, and concludes with a chapter in which he replies to and reflects on the other critical essays herein.